2003
DOI: 10.1590/s1519-566x2003000200002
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle of Retracrus johnstoni Keifer (Acari: Phytoptidae)

Abstract: Neotropical Entomology 32 (2):197-201 (2003) Ciclo de Vida de Retracrus johnstoni Keifer (Acari: Phytoptidae) RESUMO -Os ácaros Eriophyoidea estão comumente associados a palmeiras, entretanto poucas espécies têm sido relatadas causando danos econômicos nessas plantas. Uma exceção é Retracrus johnstoni Keifer, praga de Bactris gasipaes Kunth, planta utilizada na produção de palmito. R. johnstoni tem sido encontrado em grande número de arecáceas no Sudeste do Brasil. O objetivo deste trabalho foi estudar a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Results showed that P. adalius has a short developmental period; a slightly shorter or similar length of development was observed for Aculops lycopersici (Massee) (Abou-Awad 1979 ; Haque and Kawai 2003 ) and Metaculus mangiferae (Attiah) (Abou-Awad et al 2011b ). Some other species need longer periods to reach adulthood; up to 20.5 days for Retracarus johnstoni Keifer, a dangerous pest of palm trees (Gondim and de Moraes 2003 ). Juvenile development is longer for P. fructiphilus , a species closely related to P. adalius (Kassar and Amrine 1990 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that P. adalius has a short developmental period; a slightly shorter or similar length of development was observed for Aculops lycopersici (Massee) (Abou-Awad 1979 ; Haque and Kawai 2003 ) and Metaculus mangiferae (Attiah) (Abou-Awad et al 2011b ). Some other species need longer periods to reach adulthood; up to 20.5 days for Retracarus johnstoni Keifer, a dangerous pest of palm trees (Gondim and de Moraes 2003 ). Juvenile development is longer for P. fructiphilus , a species closely related to P. adalius (Kassar and Amrine 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, and despite the importance of eriophyoids, either as pests or biological agents, knowledge on their biology and ecology is limited. To date, detailed studies on the life history of eriophyoids have been performed for only a few species (Sabelis and Bruin 1996 ; Abou-Awad et al 2000 , 2005 , 2011a , b ; Ebrahim 2000 ; Shi 2001 ; Gondim and de Moraes 2003 ; Haque and Kawai 2003 ; Ansaloni and Perring 2004 ; Skoracka and Kuczyński 2004 , 2006 ; Ozman and Goolsby 2005 ; Walton et al 2010 ; Stoeva et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…200 µm, and range from 80 µm to 500 µm (Lindquist, 1996). The smallest eriophyoid mites normally only have a single egg per female at any one time (Gondim & Morales, 2003) and their males are smaller than the females (Colwell, 2000). These mites, however, are not egg-parasitoids but freeliving organisms that feed on plant tissue.…”
Section: Discussion On Insect Miniaturizationmentioning
confidence: 99%
“…The procedure developed by De Silva and Fernando (2008) to successfully mass rear Aceria guerreronis Keifer on embryo culture seedlings for up to 5 weeks offers promise for rearing of species strictly associated with young and meristematic tissues. Rearing was also indirectly handled in a few others studies (Courtin et al 2000;Schwoebel and Beiderbeck 2000;Gondim and de Moraes 2003;Skare et al 2003;Ansaloni and Perring 2004;Skoracka and Kuczyński 2004;Witt 2004;Britto et al 2008), resulting in successful multiplication of eriophyoids dedicated to various subsequent biological investigations.…”
Section: Rearing Techniquesmentioning
confidence: 99%
“…Wax secretion by adults and immatures has been recorded for Retracrus johnstoni Keifer (Gondim and de Moraes 2003). Frost (1997) showed that changes in the rate of wax production by grass-feeding A. hystrix had genetic and environmental components.…”
Section: Physiologymentioning
confidence: 99%